METHOD FOR MAKING CARBON NANOTUBE COMPOSITE - ZHOU RUI-FENG; RYO KAI; SUN YING-HUI; JIANG KAILI; FAN FENG-YAN (2011)
PROBLEM TO BE SOLVED: To provide a method for making a carbon nanotube composite. SOLUTION: The method for making a carbon nanotube composite includes: a first step of forming a carbon nanotube structure comprising a plurality of carbon nanotubes; a second step of applying a reacting liquid containing at least one kind of metal compound to the carbon nanotube structure, and immersing the carbon nanotube structure into the reacting liquid; and a third step of heating the carbon nanotube structure to which the reacting liquid is adhered in an oxide-free environment to decompose the metal compound in the reacting liquid, and forming a reinforced body in the carbon nanotube structure to form the carbon nanotube composite. COPYRIGHT: (C)2011,JPO&INPIT